Biomimetic engineering of the cardiac tissue through processing, functionalization, and biological characterization of polyester urethanes. (3rd July 2018) - Vozzi, Federico; Logrand, Federica; Cabiati, Manuela; Cicione, Claudia; Boffito, Monica; Carmagnola, Irene; Vitale, Nicoletta; Gori, Manuele; Brancaccio, Mara; Del Ry, Silvia; Gastaldi, Dario; Cattarinuzzi, Emanuele; et al.
Abstract: Three-dimensional (3D) tissue models offer new tools in the study of diseases. In the case of the engineering of cardiac muscle, a realistic goal would be the design of a scaffold able to replicate the tissue-specific architecture, mechanical properties, and chemical composition, so that it recapitulates the main functions of the tissue. This work is focused on the design and preliminary biological validation of an innovative polyester urethane (PUR) scaffold mimicking cardiac tissue properties. The porous scaffold was fabricated by thermally induced phase separation (TIPS) from poly( ε -caprolactone) diol, 1, 4-butanediisocyanate, andl -lysine ethyl ester. Morphological and mechanical scaffolds characterization was accomplished by confocal microscopy, and micro-tensile and compression techniques. Scaffolds were then functionalized with fibronectin by plasma treatment, and the surface treatment was studied by x-ray photoelectron spectroscopy, attenuated total reflectance Fourier transform infrared spectra, and contact angle measurements. Primary rat neonatal cardiomyocytes were seeded on scaffolds, and their colonization, survival, and beating activity were analyzed for 14 days. Signal transduction pathways and apoptosis involved in cells, the structural development of the heart, and its metabolism were analyzed. PUR scaffolds showed a porous-aligned structure and mechanical properties consistent with that of the myocardial tissue. Cardiomyocytes plated on the scaffolds showed a high survival rate and a stable beating activity. Serine/threonine kinase (AKT) and extracellular signal-regulated kinases (ERK) phosphorylation was higher in cardiomyocytes cultured on the PUR scaffold compared to those on tissue culture plates. Real-time polymerase chain reaction analysis showed a significant modulation at 14 days of cardiac muscle (MYH7, prepro-ET-1), hypertrophy-specific (CTGF), and metabolism-related (SLC2a1, PFKL) genes in PUR scaffolds.